(untitled) (Historia, 2021)
The integration of traditional institutions in the aftermath of colonisation and apartheid in Southern Africa has not only affected governance and jurisdiction in individual countries but has also left a lasting imprint on traditional communities and institutions. Due to migration and changing colonial borders, the Tswana chiefdom of the Bakgatla-ba-Kgafela in Botswana and in South Africa have experienced different paths of development, and both parts of the tribal entity have had to adapt to various social environments, legal frameworks and institutional setups. The research analyses the consequences of the geographical division and separate development of the Bakgatla-ba-Kgafela. Internal dynamics like adaptation, modernisation and assumption of new traditions have interacted with external factors such as the impact of legal and institutional pluralism in Botswana and South Africa. The article discusses how the Bakgatla-ba-Kgafela have dealt with these obstacles and whether cohesion has been maintained by the traditional leadership and communities. After periods of close co-operation, cross-border rule and mutual support of the tribal leadership, they are currently facing serious threats to tribal unity. Die integrasie van tradisionele instellings in die nadraai van kolonialisering en apartheid in Suidelike Afrika het nie alleen staatsbestuur en regspraak in individuele lande geraak nie, maar het ook ’n blywende stempel op tradisionele gemeenskappe en instellings afgedruk. Weens migrasie en veranderende koloniale grense het die Tswana-kapteinskap van die Bakgatla-ba-Kgafela in Botswana en in Suid-Afrika verskillende ontwikkelingsbane meegemaak, en beide dele van die stam-entiteit moes by verskeie sosiale omgewings, regsraamwerke en institusionele opsette aanpas. Die navorsing ontleed die gevolge van die geografiese verdeling en afsonderlike ontwikkeling van die Bakgatla-ba-Kgafela. Interne dinamiek soos aanpassing, modernisering en die oorneem van nuwe tradisies het opt eksterne faktore soos die impak van regs- en institusionele pluralisme in Botswana en Suid-Afrika ingewerk. Die artikel bespreek hoe die Bakgatla-ba-Kgafela hierdie struikelblokke hanteer het en of kohesie deur die tradisionele leierskap en gemeenskappebewaar is. Na tydperke van noue samewerking, oorgrens-regering en onderlinge ondersteuning van die stam-leierskap word hulle tans deur ernstige bedreigings ten opsigte van stam-eenheid in die gesig gestaar.